Learn Programming Languages Using Chatgpt - Fahmi, fahmi Nugraha (Universitas Utpadaka Swastika, 2024)
Technology is currently developing rapidly, where every year there are lots of programming languages which appears to provide solutions in creating applications or as business support Many of these programming languages require one to learn to be able to do them competing in a world of work that is now dominated by AI and machine learning so we must be able to take advantage of learning quickly using chatGPT However, someone who is truly an expert in this field is still needed to verify the correctness of the code produced